2016
DOI: 10.5815/ijisa.2016.09.03
|View full text |Cite
|
Sign up to set email alerts
|

VLSI Circuit Configuration Using Satisfiability Logic in Hopfield Network

Abstract: Very large scale integration (VLSI) circuit comprises of integrated circuit (IC) with transistors in a single chip, widely used in many sophisticated electronic devices. In our paper, we proposed VLSI circuit design by implementing satisfiability problem in Hopfield neural network as circuit verification technique. We restrict our logic construction to 2-Satisfiab ility (2-SAT) and 3-Satisfiability (3-SAT) clauses in order to suit with the transistor configuration in VLSI circuit. In addit ion, we developed VL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…The proposed work showed that information embedded in 3SAT yielded a better result for Pattern-SAT. The work by [17] utilized 3SAT integrated with an HNN to configure a Very Large-Scale Integrated (VLSI) circuit. The proposed hybrid network achieved more that 90% accuracy in terms of circuit verification.…”
Section: Introductionmentioning
confidence: 99%
“…The proposed work showed that information embedded in 3SAT yielded a better result for Pattern-SAT. The work by [17] utilized 3SAT integrated with an HNN to configure a Very Large-Scale Integrated (VLSI) circuit. The proposed hybrid network achieved more that 90% accuracy in terms of circuit verification.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, exhaustive searches are only practical for a small number of variables. For this reason, exhaustive searches in a minimal search area are only practicable for a small number of variables [12,18,28,54].…”
Section: Stage 4: Clause Evaluationmentioning
confidence: 99%
“…The cost of each country is ascertained by calculating its objectives function 12 ( , ,..., ) Np f l l l .…”
Section: Imperialist Competitive Algorithm (Ica)mentioning
confidence: 99%
See 1 more Smart Citation
“…The disadvantages of the proposed HNN model are the storage capacity [13], high computation time [14] and easily trapped in local minima [15]. Since then, the usage of logic programming in ANN has been integrated into several disciplines such as Pattern Reconstruction [16], Agent Based Modelling [17] and Circuit modelling [18]. The rapid development of logic programming in ANN was extended to accommodate real-life datasets.…”
Section: Introductionmentioning
confidence: 99%